Scrap metal management system (SMMS) / Mohd Fadhil Ibrahim - Ibrahim, Mohd Fadhil (2014)
Nowadays, a lot of criminal cases happened involve the scrap metal theft. The thief stole the scrap metal in order to get money. Today the selling of the scrap metal are widely growth. The scrap metal become valuable because it is something recyclable many times. The price of scrap metal increasing rapidly because of demand from the metal's industry. Rising copper prices in the last few days may lead buyers to believe normal business has resumed for the copper bull run. The stealing of the scrap metal become worrisome because this activity become harmful to the public. Example, they stole the drain cover on the road and it is harmful because it will lead injury to the road users. Therefore, we develop a system to propose to the government to catch the scrap metal thief and the system is Scrap Metal Management System (SMMS). The method that are used in this problem is we comes with system development. The methodology that have been used is system development method (SDM). The result is, the government or enforcement can monitor who are the seller of the scrap metal and with this system, it will reduce the scrap metal theft.